2020
DOI: 10.3988/jcn.2020.16.4.624
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcomes of Intracranial Aneurysm Associated with Moyamoya Disease

Abstract: Background and Purpose Moyamoya disease (MMD) is a rare form of intracranial stenoocclusive disease that can be associated with intracranial aneurysms. We evaluated the clinical features and outcomes of MMD-associated aneurysms while focusing on their locations. Methods Between January 1998 and December 2018 there were 1,302 adult and pediatric patients diagnosed as MMD at a single institution. These patients included 38 with 44 MMD-associated aneurysms. The MMD-associated aneurysms were classified into two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
(44 reference statements)
0
20
0
Order By: Relevance
“…22 Due to hemodynamic stress and attenuated arterial wall integrity, the main trunks of intracranial arteries can grow aneurysms. 5 In Kim et al’s 13 study of MMD-associated aneurysms, 63.6% of aneurysms were located on the main trunks of intracranial arteries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Due to hemodynamic stress and attenuated arterial wall integrity, the main trunks of intracranial arteries can grow aneurysms. 5 In Kim et al’s 13 study of MMD-associated aneurysms, 63.6% of aneurysms were located on the main trunks of intracranial arteries.…”
Section: Discussionmentioning
confidence: 99%
“…In MMD, when main trunk aneurysms were initially unruptured lesions, follow-up angiography showed that 82.1% of aneurysms had a stable status and 17.9% had a worse status. 13 Therefore, the close follow-up was necessary. 14 However, in the real world, most aneurysms in MMD cannot be found until they rupture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural clinical course of MMD-associated ACoA aneurysm remains unknown. While some researchers have stressed the devastating nature of MMD-associated aneurym, 16,17 others have suggested that such aneurysms can spontaneously disappear with the progression of MMD. 18,19 Spontaneous disappearance of ACoA aneurysm can occur in unilateral MMD if the contralateral ICA gradually becomes occluded.…”
Section: Observationsmentioning
confidence: 99%
“…They are usually located in deep areas [11], small in size and with very fragile walls, making their treatment, endovascular or surgical, extremely challenging [11,12,14]. They can also be found at the circle of Willis [9,11,15,16], where they usually have a fusiform shape [11,17] and can lead to a subarachnoid haemorrhage [11]. The prognosis in the case of this type of haemorrhage is poor [11].…”
Section: Introductionmentioning
confidence: 99%